757 Intratumoral delivery CD40 agonist antibody via novel nanofluidic drug-eluting seed reduced tumor burden of murine pancreatic ductal adenocarcinoma. (9th November 2020) - Liu, Hsuan-Chen; Viswanath, Dixita; Pol, Robin Vander; Chua, Corrine; Grattoni, Alessandro
Abstract : Background: Pancreatic adenocarcinoma (PDAC) is associated with extremely poor prognosis and a 5-year survival rate of 10% and remains a lethal malignancy. Surgical resection and combination with chemoradiotherapy are the current standard-of-care options, may improve long-term survival in localized disease; however, the majority of patients are diagnosed at advanced stage. The incorporation of immunotherapy in the treatment algorithm convenes a new era for PDAC treatment. Several immunotherapy approaches have been investigating for treating PDAC such as checkpoint inhibitors, vaccines, adoptive cell therapy, and so on. Immunotherapy has been shown as a promising therapeutic method for many cancer types; however, the complexity and immunosuppressive of the solid tumor microenvironment (TME) results in limited treatment efficacy for PDAC. Methods: To sensitize the TME in response to immunotherapy, we developed an implantable intratumoral drug delivery device, Nanofluidic Drug-Eluting Seed (NDES) can be injected via a minimally invasive trocar system that feasible for the clinical setting. NDES has shown efficiently delivered immunotherapy to murine breast cancer model and reduced tumor burden and showed low liver inflammation compared to the intraperitoneal delivery approach in the previous study. 1 2 Here, we utilized NDES for the sustained intratumoral delivery of the CD40 antibody. We compared the efficacy of NDES against intraperitoneal and intratumoral administration, which mimics conventional systemic treatment. Tumor growth was investigated for treatment efficacy. Local and systemic immune responses were assessed via flow cytometry. Results: NDES delivered CD40 significantly reduced tumor burden, some even achieved tumor clearance. Local NDES CD40 delivery approach showed a systemic increase of CD8+ and CD4+ T cells in the tumor-draining lymph node and spleen by flow cytometry. Furthermore, NDES CD40 treated mice showed an increase of CD8+ and CD4+ central memory T cells locally and systemically. We also investigated the combination with radiotherapy, no significant difference in tumor burden was observed when compared to single-agent CD40 antibody. The results indicated CD40 promotes TME response and improved treatment efficacy. Conclusions: These immunological responses demonstrate 'cold' to 'hot' tumor transformation, which translated to tumor burden reduction. Overall, NDES delivery strategy offers promise for enhancing therapeutic index and transforming the landscape of PDAC tumor therapy. References: Liu H-C, Viswanath D, Pesaresi F, et al. Potentiating antitumor efficacy through radiation and sustained intratumoral delivery of anti-CD40 and anti-PDL1. Int J Radiat Oncol Biol Phys 2020;S0360-3016(20)33745-7. Chua CYX, Jain P, et al. Nanofluidic drug-eluting seed for sustained intratumoral immunotherapy in triple negative breast cancer. J Control Release 2018;285 :23–34.